PENGGUNAAN GROUND PENETRATING RADAR (GPR) DALAM PENELITIAN ARKEOLOGI - Ida Bagus Putu Prajna Yogi (Balai Arkeologi Kalimantan Selatan, 2009)
The core of archaeological research is excavation, a destructive and unrepeatabl method employed to collect data buried underground. Today, there is a device which can reduce excavation failure and harmful impact upon archaeological date i.e. ground penetrating radar (GPR). Many archaeological research carried out abroad have been using the GPR, since it is considered one of the most effective methods to identify the condition beneath the ground before starting an excavation. Unfotunately, it is still infrequently employed in archaeological research in Indonesia. This article discussed the benefing of GPR methos for archaeological research and excavation in Indonesia.